Higher mode effects on capacity curves - Parajuli, Hari Ram; Tiwari, Suman Kumar (Journal of Innovations in Engineering Education, 2021)
The effects of higher modes on the capacity curves and their effects on the formation of plastic hinges are studied herein for regular reinforced concrete structure with no any weak or soft story having time period typically less than 1 sec. The theoretical validity of modal pushover analysis is explained with respect to elastic and inelastic systems. In this modal pushover analysis (MPA), the seismic demand due to individual terms in the modal expansion of the effective earthquake forces is determined by a pushover analysis using the inertia force distribution for each mode. The higher mode pushover curves show significant increase in base shear as well as significant decrease in roof displacement that are not detected by the first mode which is a part of FEMA-356 force distributions. To determine the difference of seismic response parameter at concerned point, local performance levels are used rather than global performance level for better accuracy. Fiber plastic hinges model is used instead of conventional lumped plastic hinge where stress-strain curves is directly applied for confined concrete to inner core concrete and unconfined stress- strain to outer concrete. Base Shear of Capacity Curve at IO performance level, inelastic beam component with compressive stress at 0.002 and 0.0038 increased by 14.52 %, 10.825 %, and 10.42 % respectively. Displacement Demand of Capacity Curve at IO performance level, inelastic beam component with compressive stress at 0.002 and 0.0038 decreased by 15.84 %, 15. 94 % and 12.86 %. It is seen that up to 3rd mode is crucial and should be amalgamate in regular structure and up to 8th mode should be amalgamate in irregular structure